Psychometric properties of the situational procrastination scale of medical undergraduates: factor structure, reliability, and validity - Wang, Chunxiao; You, You; Ahemaitijiang, Nigela; Han, Zhuo Rachel (Frontiers in Psychiatry, 2024)
Procrastination is very common among college students, but there is a lack of consistency in the relationship between procrastination and academic achievement, which might be partly caused by the limitations of previous procrastination scales. The current study constructed the Situational Procrastination Scale (SPS) with two subscales, the Academic Situational Procrastination Scale (ASPS) and the Daily Life Situational Procrastination Scale (DSPS), by adapting previous procrastination scales. The valid sample for data analysis included 2,094 medical undergraduates. Exploratory and confirmatory factor analyses revealed a four-factor structure of the ASPS and the DSPS, respectively. The ASPS included near lateness, lateness, procrastination on academic tasks before deadlines, and procrastination on academic tasks beyond deadlines, and measurement invariance across gender, household registration, and family financial status was found. The DSPS included procrastination on going out, consumption, routines, and communication, and had measurement invariance across grade, household registration, and family financial status. The results demonstrated adequate internal consistency, test-retest reliability, concurrent validity, convergent validity, and discriminant validity. Situational procrastination positively correlated with trait procrastination at a moderate or low level and negatively correlated with self-efficacy. Only procrastination on academic tasks before and beyond deadlines negatively predicted academic achievement. The SPS could measure procrastination accurately and clarify the nexus between procrastination and academic achievement, which has implications for improving the academic warning system.